Comparison of Quality of Life between Patients Undergoing Chronic Hemodialysis with Reusable Dialyzer and Single-Use Dialyzer: A Retrospective Cohort Study - Lucky Aziza Bawazier; Suhardjono Suhardjono (Interna Publishing, 2018)
Background: in Indonesia, majority of hemodialysis centers use reusable dialyzer for cost efficiency reason. Currently, there is no available data regarding the quality of life of the end stage-renal disease patient'who use reusable dialyzer measured by a standardized questionnaire, as it was stated that at molecular level, reusable dialyzer could worsen leukocyte activity and could affect patients' complaints and symptoms. Methods: this was a retrospective cohort study which involved 39 subjects. All subjects underwent hemodialysis at Cipto Mangunkusumo Hospital. The study was conducted in March - September 2017. All subjects had experienced two kinds of dialyzers, the reusable dialyzers (before 2015) and the single-use dialyzers (after 2015). Of all patients, 19 patients did not know the change of dialyzers. Subjects were interviewed with Kidney Disease Quality of Life-Short Form 36 questionnaire. Results: in kidney disease component dimension, there was a significant mean difference between reusable group (68.74; SD 13.22) and single-use group (74.87; SD 13.54) (Wilcoxon test, p=0.01). The Physical Component Summary dimension, in reusable group was 63.65; SD 27.07 and in single-use group was 69.38; SD 23.07 (Wilcoxon test, p=0.217). The Mental Component Summary dimension, in reusable group was 71.78; SD 21.54 and in single-use group was75.27; SD 22.30 (Wilcoxon test, p=0.127). Bivariate analysis and further analysis showed significant association between income less than 5 million rupiah and low quality of life (p=0.048). Conclusion: the reusable dialyzer membrane lowers the ESRD patients' quality of life influenced by another factor such as low income.